Implementation of Make a Match (MaM) Learning Model to the Nomenclature of Common Chemical Compounds on Motivation and Learning Activities of Class X SMA Negeri 1 Turi Academic Year 2019/2020 - Mutmainnah; Widinda Normalia Arlianty; Muhaimin Muhaimin; Beta Wulan Febriana (International Journal of Chemistry Education Research, 2022)
The aim of this study is to find out: 1) Determine whether or not there is a significant difference between the implementation of making a match learning model with conventional learning model to the nomenclature of common chemical compounds on learning motivation, 2) Determine whether or not there is a significant difference between the implementation of making a match learning model with conventional learning model to the nomenclature of common chemical compounds on learning activities. This research was experimental research design with Posttest Only Nonequivalent Control Group Design. The population of this study was all class X students of SMA Negeri 1 Turi in the academic year 2019/2020, with a two-class research sample, namely class X MIPA 1 and X MIPA 2. Data of concept for activity variables and learning motivation  taken by non-test methods in the form of questionnaires and observation. Data analysis techniques used the Mann Whitney type non-parametric statistical test for learning motivation variables and the Two Independent Sample T-Test type parametric statistical test for learning activity variables on nomenclature of common chemical compounds. Based on the results of the study, it can be concluded: 1) There was no significant difference between the implementation of make a match learning with conventional learning model to the nomenclature of common chemical compounds on motivation learning of class x SMA Negeri 1 Turi academic year 2019/2020; 2) There were no significant difference between the implementation of make a match learning with conventional learning model to the nomenclature of common chemical compounds on activities learning of class x SMA Negeri 1 Turi academic year 2019/2020. Keywords: make a match, learning motivation, learning activities